Biophysical Follow-up of Age-Group Swimmers During a Traditional Three-Peak Preparation Program. Issue 9 (September 2020) - Zacca, Rodrigo; Azevedo, Rui; Ramos, Valdir R.; Abraldes, José A.; Vilas-Boas, João P.; Castro, Flávio Antônio de Souza; Pyne, David B.; Fernandes, Ricardo J.
Abstract : Abstract: Zacca, R, Azevedo, R, Ramos, VR, Abraldes, JA, Vilas-Boas, JP, Castro, FAdS, Pyne, DB, and Fernandes, RJ. Biophysical follow-up of age-group swimmers during a traditional three-peak preparation program. J Strength Cond Res 34(9): 2585–2595, 2020—The aim of this study was to quantify changes and contributions of bioenergetic, technique, and anthropometric profiles across a traditional 3-peak swimming season. Twenty-four age-group swimmers (11 boys: 15 years 6 months ± 1 year 1 month; 13 girls: 14 years 5 months ± 10 months) of equal maturational stage were monitored through a 400-m test in front crawl (T400). Bioenergetic, technique, and anthropometric characteristics were compared before and after macrocycles I, II and III. Sex interaction was verified only for amplitude of the fast oxygen uptake component and height (moderate). Multiple linear regressions and principal component analysis were used to identify the most influential variables and the relative contribution of each domain (bioenergetics, technique, and anthropometrics) to changes in swimming performance of T400. The relative contributions for the performance of T400 after macrocycles I, II, and III were, respectively, 6, 18, and 27% for bioenergetics, 88, 69, and 54% for technique, and 6, 13, and 20% for anthropometrics. Technique was the biggest contributor (71%) for changes in the performance of T400 over the training season, followed by bioenergetics (17%) and anthropometrics (12%). Technique played the main role during the competitive season, regardless of gradual increase in the contribution of bioenergetics and anthropometrics. Despite that, bioenergetics and technique are closely connected, thus a powerful and endurable metabolic base and cannot be overlooked. Changes and contribution of bioenergetics, technique, and anthropometrics on age-group swimmers' performance over a traditional 3-peak swimming season could be described by the T400 swimming test, providing a comprehensive biophysical overview of the main contributors to swimming performance.